2014
DOI: 10.1016/j.apsb.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental aspects of solid dispersion technology for poorly soluble drugs

Abstract: The solid dispersion has become an established solubilization technology for poorly water soluble drugs. Since a solid dispersion is basically a drug–polymer two-component system, the drug–polymer interaction is the determining factor in its design and performance. In this review, we summarize our current understanding of solid dispersions both in the solid state and in dissolution, emphasizing the fundamental aspects of this important technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
286
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(301 citation statements)
references
References 50 publications
5
286
0
10
Order By: Relevance
“…Converting the drug into the amorphous state and the drug-carrier interactions are the instrumental factors in the design and performance of the relevant solid dispersion (Graeser et al, 2010;Huang and Dai, 2014). Because of the higher Gibbs free energy of the amorphous form, the energy required to dissolve the drug from amorphous state is far less than that required for the equivalent amount from the crystalline state (Hancock and Zografi, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Converting the drug into the amorphous state and the drug-carrier interactions are the instrumental factors in the design and performance of the relevant solid dispersion (Graeser et al, 2010;Huang and Dai, 2014). Because of the higher Gibbs free energy of the amorphous form, the energy required to dissolve the drug from amorphous state is far less than that required for the equivalent amount from the crystalline state (Hancock and Zografi, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Differential scanning calorimetry studies confirmed encapsulation of the drug within the nanoparticles. The decrease in glass t ransition temperature with increased drug loading shown in Table 2 suggests a solid dispersion of digoxin in the polymer matrix [30]. Because the glass transition temperature of the polymeric nanoparticles is below 37°C, the polymers would be in an elastomeric, rubbery state at physiological temperature, rather than in a rigid, glassy state.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…21 EM is practically insoluble moiety belonging to the BCS-II class. Therefore, SDs of EM were prepared by hot melt method, solvent evaporation method and kneading method.…”
Section: Preparation Of Solid Dispersions (Sds)mentioning
confidence: 99%